2011
DOI: 10.1166/jnn.2011.3946
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Cellular Biocompatibility of Two Nanophase Hydroxyapatite with Different Ca/P Ratio

Abstract: The cellular biocompatibility of two types of nanophase hydroxyapatites including nanophase standard hydroxyapatite (n-HA) and nanophase calcium deficient hydroxyapatite (n-CDHA) synthesized by a wet chemical method were assessed using primary cultured osteoblasts. Cytotoxicity of both materials was investigated with L929 cell line. The MTT method was used to evaluate the proliferation of osteoblasts on the third day and ALP activity assay was carried out on the fifth day. SEM was used to observe the morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
0
11
0
1
Order By: Relevance
“…Generally, the enhancement of mechanical property suppresses the bioactivity of BCP ceramics, so it is urgent to seek a balance between the enhancement of mechanical characteristics and the improvement of biological properties in BCP ceramics. Previous studies have proved that CDHA shows excellent bioactivity due to its bone‐like mineral 16‐18 . Our previous works further demonstrated that the addition of calcium alginate could stabilize CDHA in BCP ceramics and enhance their biological properties, 20,21 but the mechanical property of the obtained BCP ceramics was unsatisfied.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Generally, the enhancement of mechanical property suppresses the bioactivity of BCP ceramics, so it is urgent to seek a balance between the enhancement of mechanical characteristics and the improvement of biological properties in BCP ceramics. Previous studies have proved that CDHA shows excellent bioactivity due to its bone‐like mineral 16‐18 . Our previous works further demonstrated that the addition of calcium alginate could stabilize CDHA in BCP ceramics and enhance their biological properties, 20,21 but the mechanical property of the obtained BCP ceramics was unsatisfied.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have proved that CDHA shows excellent bioactivity due to its bone-like mineral. [16][17][18] Our previous works further demonstrated that the addition of calcium alginate could stabilize CDHA in BCP ceramics and enhance their biological properties, 20,21 but the mechanical property of the obtained BCP ceramics was unsatisfied. In this study, in order to simultaneously improve the mechanical property and bioactivity of BCP ceramics, we introduced an effective approach by adding CaO, and the effects of CaO on the sintering behaviors and biological performances of BCP ceramics were systemically investigated.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Ca/P比, 并且可以加速成骨细胞MC3T3-E1的初始黏 附, 增殖和分化 [14] . 通过研究成骨细胞对普通nHA 和钙缺陷nHA两种材料的生物效应, 发现其对成骨 细胞的活性和ALP的产生均有促进作用, 钙缺陷nHA 的成骨分化能力要显著高于普通nHA [15] . 单一nHA 支架的粒径对骨细胞的生物学功能也起到重要的调 控作用.…”
Section: 过酸刻蚀技术 发现30%磷酸蚀刻可以有效地改变unclassified